2013
DOI: 10.1007/s12182-013-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of noble gases in natural gas and their application in tracing natural gas migration in the middle part of the western Sichuan Depression, China

Abstract: Noble gases in natural gas, from Xiaoquan, Xinchang, Hexingchang and Fenggu gas the volume content of crustal noble gases accounts for 97.9% to 99.7% of the total noble gas content, indicating that the noble gases in the study area are very largely derived from the crust. Moreover, the 40 light hydrocarbons. Due to the short migration distance, the separation of 4 He and 40 4 He and 40 Ar in Middle and Upper Jurassic natural Jurassic formations. In addition, the variation trends of 3 He/ 4 13 C 1 value indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These gases were derived from sedimentary organic matter and their characteristics also indicate oil-associated gases, which were produced in well CK1. These characteristics differ from those of the coal gases that originated from the Late Triassic Xujiahe Formation (Shen et al, 1995;Katz et al, 2008;Wang et al, 2013a) (Fig. 17).…”
Section: He-ne-ar Isotopesmentioning
confidence: 70%
See 1 more Smart Citation
“…These gases were derived from sedimentary organic matter and their characteristics also indicate oil-associated gases, which were produced in well CK1. These characteristics differ from those of the coal gases that originated from the Late Triassic Xujiahe Formation (Shen et al, 1995;Katz et al, 2008;Wang et al, 2013a) (Fig. 17).…”
Section: He-ne-ar Isotopesmentioning
confidence: 70%
“…17. Classification of the isotopic compositions of the He and Ar of the natural gases from well CK1 (Shen et al, 1995;Wang et al, 2013a).…”
Section: He-ne-ar Isotopesmentioning
confidence: 99%
“…1) Deep inorganic CO 2 , desulfurization, atmospheric water leaching and NaHCO 3 -type water Wang et al (2013) studied the rare gas content and isotopes of He, Ne, and Ar in the tight sandstone gas of the Upper Triassic Xujiahe Formation in the western Sichuan Depression and confirmed that the Upper Triassic stratigraphic fluid in this area has no contribution from deep and mantle-derived materials. Therefore, the possibility of deep inorganic CO 2 entering the formation water to form NaHCO 3 -type water can be denied.…”
Section: Formation Water Typementioning
confidence: 83%
“…As shown in Table 2, the 3 He/ 4 He value of CO 2 reservoirs in the Pingfangwang, Huagou, and Yangxin gas fields in the Jiyang Depression was high (3.55-4.49 9 10 -6 ), and R/Ra was 2.5-3.2, indicating a mixed He origin of mantle genesis and crust genesis (Wang et al 2013). The isotopic analysis of rare gases and CO 2 indicated that the highly concentrated CO 2 gas reservoir in the Jiyang Depression originated from magma-mantle degassing (Hunt et al 2012).…”
Section: Abiogenic Gasmentioning
confidence: 97%